α-Amylase, α-glucosidase and aldose reductase inhibitory and molecular docking studies on Tinospora cordifolia (Guduchi) leaf extract - Hemlata Janardhan Bhosale; Shailesh Vaijeenath Mamdapure; Ramdas Balaji Panchal; Umesh Pravin Dhuldhaj (SpringerOpen, 2024)
Abstract Background Type II diabetes mellitus is posing a severe health threat throughout the globe due to its associated pathophysiological risks and high mortality rate. Carbohydrate catabolic enzymes, including α-amylase, α-glucosidase and aldose reductase, play an important role in the development of diabetes. The natural or synthetic inhibitors of these enzymes are crucial in reducing diabetes and its related complications. Tinospora cordifolia is a plant of great significance in Ayurveda due to its unique biological activities, including anti-diabetic properties. The present study aims to identify the active constituents of T. cordifolia leaves and evaluate the in vitro inhibitory potential of its ethanol extract constituents against α-amylase, α-glucosidase and aldose reductase activities. Results The ethanolic leaf extract of T. cordifolia inhibited the activities of α-amylase, α-glucosidase and aldose reductase in a dose-dependent manner. It was on par  with the standard inhibitors acarbose and quercetin. At 5 mg/ml, the noted % inhibition values of extract were 69.27 ± 0.17, 67.8 ± 0.26 and 62.55 ± 0.24, respectively, for α-amylase, α-glucosidase and aldose reductase. Using GC-MS analysis, neophytadiene, γ-sitosterol, phytol, phytyl palmitate, and phytyl acetate were identified as prominent constituents of the ethanolic extract. Based on molecular docking and ADME analysis, γ-sitosterol was found as the major reactive phytoconstituent, which showed the highest inhibitory potential against α-amylase, α-glucosidase and aldose reductase activities. Conclusions The present study identified γ-sitosterol as triplet inhibitor of α-amylase, α-glucosidase and aldose reductase and affirmed the ethno-medicinal significance of T. cordifolia leaves in the development of new anti-diabetic leads.